The Contribution of Sense of Purpose to Subjective Wellbeing: A Systematic Literature Review - Heni Saidah; Azam Syukur Rahmatullah; Halim Purnomo (Journal of General Education and Humanities, 2026)
This systematic review synthesizes the contribution of sense of purpose to subjective wellbeing (SWB) and validates it through a bibliometric analysis of keyword co-occurrence. Using a Systematic-oriented Literature Review approach based on the PRISMA protocol, searches were conducted on the Scopus database and Google Scholar for publications in 2021–2025, resulting in 16 articles that met the inclusion criteria and were thematically analyzed, while the conceptual structure of the research field was validated through keyword co-occurrence analysis using VOSviewer against the initial recording of Scopus search results. The results of the thematic analysis identified six themes: health and aging; spirituality and existential wellbeing; sense of purpose as post-adversity psychological capital; socio-structural determinants; meaningful activities in work and social participation; and family and interpersonal relationships. In most themes, sense of purpose appears to act as a psychological mechanism linking external determinants to SWB. However, relationship patterns and directions vary across contexts and should be interpreted with caution given the dominance of cross-sectional design. Bibliometric analysis confirms the structural distinction between predictor and outcome keywords, but reveals minimal direct link strength between the two constructs—indicating terminological fragmentation, not weak substantive linkage. These findings confirm the need to consolidate terminology and adopt a longitudinal design in future studies, and provide an initial basis for interventions to strengthen the sense of purpose during life transitions.